An investigation into amaXhosa new initiates' masculine identity construction, mediation and negotiation: implications for the Life Orientation Curriculum - Mdaka, Sizwe (Rhodes University, Faculty of Education, Department of Education, 2019)
This study asked questions about dominant discourses shaping new amaXhosa initiates masculine identities. In particular, it asked questions on the interface between tradition and modern values and how the new initiates negotiate these in constructing masculine identities and the implications this has for schooling (and specifically LO classes). This was a qualitative case study that relied on multiple sources of data including individual and focus groups interview with AmaXhosa new initiates as well as individual interviews with teachers. The study also included classroom observations of Life Orientation classes as the selected schools. Initially, informal discussions with the new initiates were held to gain insights on their perspective of initiation schools. The findings of this study revealed three broad themes. The first was that normative masculine conceptions and manhood, with particular attention paid to constructions of manhood and masculine identity and their relation to emotional display, men as breadwinners and family providers, marriage, and heterosexuality and fatherhood. The second one was on gender space and power in the classroom which revealed masculine performance inside and outside the classroom, and the role played by sitting positions and spatial arrangements as a discursive spaces for the construction of particular masculine identities. The third related the curriculum in practice versus the stated LO curriculum and revealed a disjuncture between the two. With teachers tolerating the traditional male structures and behaviours in the classroom, despite being in conflict with the stated LO curriculum core messages on gender, patriarchy and equality, intentionally or unintentionally select a position of collusion rather than disruption of these classroom behaviours. The study results highlight the complex social space that new initiates inhabit in order to make meaning of their masculine identities, and the challenges for teachers and schools in mediating between the traditional values and behaviours of some leaners, some of which are in conflict with the values and behaviours espoused by the LO curriculum and the modernizing project goals of SA education and the Constitution.
Keywords: Xhosa (African people) -- Rites and ceremonies; Xhosa (African people) -- Social life and customs; Initiation rites -- South Africa -- Eastern Cape; Masculinity -- South Africa -- Eastern Cape; Life skills -- Study and teaching -- South Africa -- Eastern Cape -- Case studies; Life skills -- Study and teaching -- South Africa -- Curricula; Men -- Identity -- South Africa; Boys -- Education -- South Africa; Gender identity in education -- South Africa